Application of the Principle of Equality Before the Law in the Practice of Investigating Criminal Cases by General Criminal Investigation Investigators at the Memberamo Raya Resort Police - Yohanis Sudiman Bakti; Peter Paulus Ell (Faculty of Law, Universitas Pekalongan, 2022)
Equality before the law is positioned by the UN as the first indicator or main characteristic of a democratic rule of law, in the sense that there must be no arbitrariness, so that someone can only be punished if they violate the law, have equal standing before the law, and are good for the people. ordinary and for officials. However, in practice, what was hoped for has not been fully realized. Moreover, this is related to the application of the principle of equality before the law. The problem in this research is that the process of examining criminal cases by investigators from the Memberamo Raya Police Criminal Investigation Unit certainly cannot be carried out according to plan. It should be, because of various factors and reasons behind it, both in terms of the law enforcement system as a whole, structurally, as well as morally or mentally. The type of research used is Normative Juridical research methods and Empirical Juridical research methods. The research results obtained are that the application of the principle of equality before the law has not been implemented properly by the Memberamo Raya Resort Police Criminal Investigation Investigators, in the practice of examining general criminal cases. In the practice of examining general criminal cases, there are three investigators from the Memberamo Raya Police Criminal Investigation Unit. The main factors that hinder the application of the principle of equality before the law are first, limited human resources for investigators, both in terms of quality and quantity; second, the minimal budget for investigative operational costs; and third, demands for resolution of criminal cases based on the customs of local customary law communities